Groundwater Vulnerability towards Pollution in Area Around the Piyungan Landfill, Bantul Regency, D. I. Yogyakarta - Asrifah, RR. Dina; Widiarti, Ika Wahyuning; Widhiananto, Praditya Anggi; Ni’ma, Lailiyatun; Rahman, Dzulfiqar Izzatur; Jwalita, Aliendina; Romizah, Hafidz (RSF Conference Series: Engineering and Technology, 2022)
The Piyungan landfill is located in Bantul Regency, Daerah Istimewa Yogyakarta, still uses an open dumping system. The open dumping system produced more quantity of leachate from other systems. Leachate spreads to the ground and seeps into the ground to the groundwater surface. These conditions have an impact on the environment. This study aims to assess the groundwater vulnerability to leachate contamination in the area around the Piyungan landfill. The research method used is survey and mapping, and data analysis is carried out using the Le Grand method. Geographic Information System (GIS) is also used to visualize data into maps. The Le Grand method considers as many as 5 physical environmental parameters, including the groundwater depth, absorption above ground, aquifer permeability, groundwater slope, and horizontal distance of wells with pollutant sources. Next, scoring is carried out for each of these parameters, and then a groundwater vulnerability map is made using the overlay method. The results of the study were three classes of the potential vulnerability of groundwater pollutions. That were large pollution potential (may or may be polluted), medium pollution potential (maybe polluted but slightly), and small pollution potential (very difficult to pollute).